KESEMBUHAN MENTAL MELALUI BIMBINGAN TRAUMATIK PASCA KONFLIK KEKERASAN: STUDI PADA MASYARAKAT MUSLIM DI THAILAND SELATAN [MENTAL HEALING THROUGH TRAUMATIC COUNSELING AFTER VIOLENT CONFLICT: A STUDY OF MUSLIM COMMUNITY IN SOUTHERN THAILAND] - Waedoyee, Miss Humaira; Saragi, Muhammad Putra Dinata (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2025)
This research aims to find out: (1) an overview of the forms of trauma experienced by the Patani Muslim community after the violent conflict in Southern Thailand, (2) how the mental recovery of Muslim communities after violent conflict using traumatic guidance in Southern Thailand, and (3) obstacles to the mental recovery of Muslim communities after violent conflict using traumatic guidance in Southern Thailand. This research uses a qualitative method with a descriptive approach through field research techniques. The participants of this research were victims who experienced post-conflict violence trauma and counselors at the Patani Women's Association organization. The data collection technique used observation, interview and documentation techniques. This research data analysis technique was carried out by reducing data, presenting data, and drawing conclusions. The results of this study indicate that: (1) the form of trauma experienced by post-conflict victims in South Tahiland is in the form of physical and psychological trauma, (2) the process of mental healing of Muslim communities after violent conflict using traumatic guidance is carried out using the motivational interviewing counseling method which consists of 4 stages, namely building involvement (engaging), focusing goals (focusing), evoking motivation (evoking), and planning changes (planning), (3) The obstacles to the implementation of this traumatic guidance are the lack of social support from the victim's family relatives and emotional disturbances or unstable behavior of the victim.